2021
DOI: 10.1108/ijssp-01-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Social stigma in time of COVID-19 pandemic: evidence from India

Abstract: PurposeThe stigmatisation of COVID-19 patients or suspected cases is a matter of grave concern across the world, including India. Today, COVID-19 patients or suspected cases are being stigmatised or labelled as “corona carrier” and “corona spreader” because of which they are facing social rejection, mental torture, abusive behaviour and violence in the society. The objectives of the present study are to examine the nature of stigma construction in Indian society during COVID-19 pandemic and to explore its outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Media. Media factors (e.g., [social] media use 21,62 , lack of public health information 64 , and fake news 78 ) can influence stigma toward (suspected) patients and survivors in two ways: (1) low-quality and poorly regulated messages in the media (e.g., misinformation, and irresponsible reporting) may create misconceptions about COVID-19, aggravating stigma toward (suspected) patients and survivors, and (2) (suspected) patients and survivors' frequent use of media may increase their stigma perceptions due to exposure to misinformation and stigmatizing messages in the media.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Media. Media factors (e.g., [social] media use 21,62 , lack of public health information 64 , and fake news 78 ) can influence stigma toward (suspected) patients and survivors in two ways: (1) low-quality and poorly regulated messages in the media (e.g., misinformation, and irresponsible reporting) may create misconceptions about COVID-19, aggravating stigma toward (suspected) patients and survivors, and (2) (suspected) patients and survivors' frequent use of media may increase their stigma perceptions due to exposure to misinformation and stigmatizing messages in the media.…”
Section: Contextmentioning
confidence: 99%
“…One qualitative study 33 and one review 64 showed that lack of COVID-19 information in the media creates fear and uncertainty, which aggravate stigma toward (suspected) patients and survivors. Misinformation and fake news in the media also create misconceptions about COVID-19, which also contribute to stigma toward (suspected) patients and survivors 33,63,78 . In addition, a qualitative study showed that patients tend to blame irresponsible media reporting (e.g., disclosure of personal information, and false allegation) as the main driver of stigma toward them 79 .…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, so many myths have been spread about COVID-19 pandemic, which resulted in a negative attitude in the person’s behaviour toward others or, more specifically, towards the sick person (Patel & Kumar, 2021a). People have been abused and subjected to emotional, verbal and physical abuse because of the negativity of this COVID-19 pandemic (Patel & Kumar, 2021a; Sahoo & Patel, 2021b). All these factors contributed to a person’s increasing distance from his or her family and society.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher discovered common keywords used by Indian journalists when reporting on similar instances from offline newspapers and utilised those terms to search for material on internet platforms. Utilise keywords such as banned, threat, entrance, abuse, denial, stigma, assault and discrimination while doing an internet search for elder abuse induced by COVID-19 (Sahoo & Patel, 2021b).…”
Section: Introductionmentioning
confidence: 99%